Extraction of lipids with supercritical CO2 and downstream processing from grass-clover products from a green biorefinery demonstration platform - Damian E.L. Fetzer; Jose A.P. Coelho; Morten Ambye-Jensen (Journal of CO2 Utilization)
Grass-clover is one of the main biomass crops in northern Europe relevant for green biorefining to produce protein feed ingredients. The present study investigated the unique combination of a green biorefinery platform and supercritical carbon dioxide (scCO2) to extract lipids and biocompounds besides improving the downstream process from grass-clover leaf protein concentrate (LPC) and grass-clover fibrous press cake (FPC). Grass-clover was harvested and processed on a green biorefinery demonstration platform to yield both LPC and FPC. Then, supercritical CO2 was used by a design of experiments (DoE) method utilizing two factors (temperature and pressure) for process and optimization to obtain the extracts from LPC. Oil extraction yields from 5.41 % to 8.20 % based on dry matter was obtained. The best experimental conditions of 357.1 K and 50 MPa, were obtained for LPC oil extraction and were applied to extract oil from FPC, achieving 2.5 % oil extract. The scCO2 extracts contained 1,4-Eicosadiene, Neophytadiene, and Phytol as the main compounds, including lipid rich in omega-3 polyunsaturated fatty acids, which also contains phenolic and flavonoid compounds in the extracts. Protein concentration increases on LPC and PFC after defatting extractions. In conclusion, the integration in a green biorefining process with scCO2 showed extracts rich in lipids that are generally used in different food/pharmaceutical applications and, at the same time, served as a downstream process, increasing the protein content in the LPC. ScCO2 of FPC generated lignocellulosic rich in lipid-free fibers that can be used in further cascade valorization to produce biomaterials and chemicals.